2012
DOI: 10.1509/jm.10.0537
|View full text |Cite
|
Sign up to set email alerts
|

Can Automated Group Recommender Systems Help Consumers Make Better Choices?

Abstract: Because hedonic products consist predominantly of experience attributes, often with many available alternatives, choosing the "right" one is a demanding task for consumers. Decision making becomes even more difficult when a group, instead of an individual consumer, will consume the product, as is regularly the case for hedonic offerings such as movies, opera performances, and wine. Noting the prevalence of automated recommender systems as decision aids, the authors investigate the power of group recommender sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…As presented in Appendix B (Supplementary material), Table B1 (first column), there was a significant two‐way interaction between early adoption and need for uniqueness ( β = .33, t (79) = 3.49, p < .01). To gain a deeper understanding of this interaction, we ran a spotlight analysis (Aiken & West, 1991; Fitzsimons, 2008; Hennig‐Thurau, Merchand, & Marx, 2012; Spiller, Fitzsimons, Lynch, & McClelland, 2013). Consistent with H1a, among early adopters (one SD above the mean), the dilemma was more intense when need for uniqueness was high (one SD above the mean) versus low (one SD below the mean) ( M = 2.69 vs. M = .77, β = .74, t (79) = 5.93, p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Appendix B (Supplementary material), Table B1 (first column), there was a significant two‐way interaction between early adoption and need for uniqueness ( β = .33, t (79) = 3.49, p < .01). To gain a deeper understanding of this interaction, we ran a spotlight analysis (Aiken & West, 1991; Fitzsimons, 2008; Hennig‐Thurau, Merchand, & Marx, 2012; Spiller, Fitzsimons, Lynch, & McClelland, 2013). Consistent with H1a, among early adopters (one SD above the mean), the dilemma was more intense when need for uniqueness was high (one SD above the mean) versus low (one SD below the mean) ( M = 2.69 vs. M = .77, β = .74, t (79) = 5.93, p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Recommender systems have become the hallmark of modern eCommerce platforms. These systems are touted as sales support tools that help consumers identify their ideal product from among the vast variety sold by an eCommerce platform (Hennig-Thurau et al, 2012). It has been reported that over 35% of sales on Amazon.com and more than 60% of the rentals on Netix result from recommendations (Fleder et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They generate personalized predictions about product liking, by filtering the past behavior and preference statements of consumers. [21] The social engineering technique, where trust is exchanged for reputation, became a digital version known as digital recommendation marketing, so that digital techniques and social measures are able to become two sides of the same marketing coin.…”
Section: ) Marketing Intelligence As Recommendation Marketing and Dymentioning
confidence: 99%